1999
DOI: 10.1073/pnas.96.17.9873
|View full text |Cite
|
Sign up to set email alerts
|

CoREST: A functional corepressor required for regulation of neural-specific gene expression

Abstract: Several genes encoding proteins critical to the neuronal phenotype, such as the brain type II sodium channel gene, are expressed to high levels only in neurons. This cell specificity is due, in part, to long-term repression in nonneural cells mediated by the repressor protein REST͞NRSF (RE1 silencing transcription factor͞neural-restrictive silencing factor). We show here that CoREST, a newly identified human protein, functions as a corepressor for REST. A single zinc finger motif in REST is required for A larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
374
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(382 citation statements)
references
References 25 publications
7
374
0
1
Order By: Relevance
“…RCOR1, target of miR-432, co-operating with transcriptional repressor REST and other transcription regulators silences expression of neuronal genes in non-neuronal cells and neural stem cells (NSCs) [52]. Recently, it has been shown that a large number of genes might be regulated by RCOR1 independent of REST.…”
Section: Discussionmentioning
confidence: 99%
“…RCOR1, target of miR-432, co-operating with transcriptional repressor REST and other transcription regulators silences expression of neuronal genes in non-neuronal cells and neural stem cells (NSCs) [52]. Recently, it has been shown that a large number of genes might be regulated by RCOR1 independent of REST.…”
Section: Discussionmentioning
confidence: 99%
“…REST binds the RE1 element of target genes and recruits CoREST (Andres et al, 1999;Ballas et al, 2001) and mSin3A (Naruse et al, 1999;Huang et al, 1999;Grimes et al, 2000;Roopra et al, 2001), corepressor platforms which in turn recruit HDACs-1 and 2. HDACs deacetylate core histone proteins and affect dynamic and reversible gene silencing (Roopra et al, 2001;Ooi and Wood, 2007).…”
Section: Transcriptional Regulation By Rest During Strokementioning
confidence: 99%
“…However, equally important mechanisms controlling concurrent extrasynaptic down-regulation or repression of utrophin-A in myofibers that must occur to achieve expression at the NMJ rather than generalized expression throughout the sarcolemma remain unaddressed. Mechanistic clues arise from studies illustrating that restriction of neuronal sodium channel expression to the nervous system is partly due to RE-1 silencing transcription factor/neuronal-restricted silencing factor binding to a repressor element (Andres et al, 1999;Ballas et al, 2001;Lunyak et al, 2002). Additionally an N-box-mediated silencing mechanism has been suggested for nACHR subunit expression in extrasynaptic regions of muscle (Koike et al, 1995).…”
mentioning
confidence: 99%